How Prepared Are Nigerian Schools for Ebola Virus Disease Prevention and Control? - Adebimpe Wasiu Olalekan; Efuntoye Adeola (Ubiquity Press, 2015)
Background Nigeria was one of the West African countries gripped by the fear of the spread of the Ebola virus disease (EVD), leading to a long period of delay in resumption of primary and secondary schools for academic activities in September 2014. The aim of this study was to assess the preparedness of schools in the north central region of Nigeria toward EVD prevention and control within 1 month of resumption of schools. Methods This was a descriptive cross-sectional study among 76 schools selected using a multistage sampling method. Research instruments were self-administered, semi-structured questionnaires. Data was analyzed using the SPSS software version 17.0. Findings Half (38) of the schools reported that some of the children could have traveled to EVD-infected areas during the holiday period; 77.6% (59) had their teachers formally trained on EVD prevention and control before resumption; 50% (38) set up a committee on EVD prevention; and 62.9% (63) carried out awareness-raising activities on school assembly ground. Based on some preventive measures criteria, 55.2% (42) were categorized ready, whereas 44.7% (34) were not ready for EVD prevention and control within 1 month of resumption of students back to school. About 76.3% (58) said they would like to sustain these EVD prevention efforts; 14.5% (11) would like to sustain such efforts at least until the end of the present term. Determinants of readiness for EVD prevention and control include being a private school, being an urban school, belief that children could have traveled to an EVD-infected area, and school having standard operating procedure or policy guidelines on EVD prevention and control. Conclusion The persistent call for postponement of school resumption might have been due to the unpreparedness of many of schools to meet EVD prevention and control guidelines. Schools need to take more proactive and sustainable measures toward effective control of the ongoing epidemic and prevention of future occurrences.